Development of user interface for vibration measurement - Khaliswaran, Keresnan (2012)
Today’s industry uses increasingly complex machince, some with extremely demanding performance criteria. Failed machine can lead to economic loss and safety problems due to unexpected production stoppages. Fault diagnosis in the condition monitoring of these machines is crucial for increasing machinery availability and reliability.Fault diagnosis of machinery is often a difficult and daunting task. To be truly effective, the process needs to be analysis to reduce the reliance on manual data interpretation. It is the aim of this research to analysis this process using data from machinery vibrations. This thesis focuses on the development, and application of an analysis diagnosis procedure for rolling elements bearing faults. Rolling element bearings are representative in most industrial rotating machinery. Besides, these elements can also be tested economically in the laboratory using relatively simple test rigs.Novel moden signal processing method were applied to vibration signals collected from rolling elements tests. This included time-frequency signal processing techniques such as FFT.